2005
DOI: 10.1890/04-1075
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Constraints on a Global Relationship Among Leaf and Root Traits of Grasses

Abstract: Uncertainties regarding the relationships between leaf and root traits have impeded an integrated understanding of plant evolution and the efficient parameterization of ecosystem models. We measured key root and leaf traits of grasses from 77 sites in four grassland regions of the world (New Zealand, Australia, South Africa, North America). Within each region, the relationships among leaf traits paralleled those among root traits. Plants with low root or leaf N concentrations had roots or leaves with high tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
194
6
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 213 publications
(233 citation statements)
references
References 24 publications
29
194
6
4
Order By: Relevance
“…Typically, plant leaves are used as an index of whole-plant δ 15 N. Although differences often exist among leaves, roots, and stems (Kolb and Evans 2002), the N isotope ratios generally correlate among plant fractions and any average differences are generally relatively minor. For example, across 90 grass species collected from 67 sites in four grassland regions of the world, the δ 15 N of leaves averaged just 0.3 ‰ less than those of roots compared to a range of 18 ‰ for leaves and 14 ‰ for roots (Craine et al 2005). Similarly, Dijkstra et al (2003) reported differences in δ 15 N of <1 ‰ between leaves and roots of natural meadows and forests in North America, with direction and magnitude of the differences depending on the functional type (forbs, legumes or grasses).…”
Section: Plant N Isotopesmentioning
confidence: 99%
“…Typically, plant leaves are used as an index of whole-plant δ 15 N. Although differences often exist among leaves, roots, and stems (Kolb and Evans 2002), the N isotope ratios generally correlate among plant fractions and any average differences are generally relatively minor. For example, across 90 grass species collected from 67 sites in four grassland regions of the world, the δ 15 N of leaves averaged just 0.3 ‰ less than those of roots compared to a range of 18 ‰ for leaves and 14 ‰ for roots (Craine et al 2005). Similarly, Dijkstra et al (2003) reported differences in δ 15 N of <1 ‰ between leaves and roots of natural meadows and forests in North America, with direction and magnitude of the differences depending on the functional type (forbs, legumes or grasses).…”
Section: Plant N Isotopesmentioning
confidence: 99%
“…However, previous studies have mostly focused on the family or functional group level [Han et al, 2005]. Therefore, more information on the N:P stoichiometry, particularly for plant belowground parts at the genus or species level, is needed for better understanding potential responses and feedback of terrestrial nutrient cycling to climate change [Craine and Lee, 2003;Craine et al, 2005;Liu et al, 2010;Yuan et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…It was not clear whether multicollinearity was controlled but they found that after controlling for variations in N, foliar δ 15 N decreased with an increase in P and in N × P. We used the same model to fit our intra-plant dataset without consideration of multicollinearity and found that foliar δ 15 N decreased with both N and P but increased with N × P. Thus controlling multicollinearity is important for ascertaining relationships between δ 15 N and nutrient contents due to correlations between contents of different nutrients. Positive foliar correlations of δ 15 N with N have been reported in studies at smaller scales as well (e.g., Martinelli et al, 1999;Hobbie et al, 2000;Craine et al, 2005). In addition, reported a positive correlation for root tips.…”
Section: Comparison With Reported Inter-plant Relationshipsmentioning
confidence: 56%
“…As a result, the variations in the relative abundance of 15 N to 14 N, quantified as δ 15 N, of plants contain rich information about these processes (Högberg, 1997;Robinson, 2001;Evans, 2001;Dawson et al, 2002). For this reason, δ 15 N is often considered an integrator of terrestrial N cycling, and numerous studies have analyzed natural variations in plant δ 15 N across disturbance and successional stages (e.g., Hobbie et al, 2000;Wang et al, 2007;Resco et al, 2011;Hyodo et al, 2013), climate and topoedaphic gradients (e.g., Austin and Sala, 1999;Schulze et al, 1998;Martinelli et al, 1999;Amundson et al, 2003;Craine et al, 2005Craine et al, , 2009Bai et al, 2009), species (e.g., Cernusak et al, 2009;Gubsch et al, 2011), and types of mycorrhizal fungi Hobbie and Hög-berg, 2012). Other studies have used δ 15 N as an indicator of relative N and phosphorus (P) availability and limitation on plant growth (McKee et al, 2002;Wigand et al, 2007;Inglett et al, 2007;Mayor et al, 2014).…”
Section: Introductionmentioning
confidence: 99%